Europe in the World from 1350 to 1650 - Mukherjee, Rila. author. aut Link
XXIX, 409 p. 16 illus., 15 illus. in color.
Keywords: This book covers both European and global History from 1350 to 1650. The eight modules in the textbook offer an all-encompassing perspective on European history and a parallel understanding of world history, establishing a holistic framework of the events narrated. It provides a conceptual framework for understanding the factors that led to the rise of the modern West. The textbook offers maps, tables, and illustrations to quickly comprehend and recollect significant events and their causes and consequences in Europe’s transformation from medieval to modern maps. The textbook covers political, economic, intellectual, and social history from 1350 to 1650. Each module carries suggested questions and exercises to achieve greater interactive learning. The textbook serves as a convenient source of information for advanced readers and upper undergraduates in history to understand the genesis of modern Europe from multiple sources, perspectives, and languages.